1977
DOI: 10.1111/j.1365-2621.1977.tb12676.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants From Rosemary and Sage

Abstract: The presence of antioxidants in spices, specifically Rosemary and sage, is well known. However, the extracts of such spices usually have a strong odor and bitter taste and therefore cannot be used in most food products. This paper reports a patented process for the extraction of Rosemary and sage followed by a vacuum steam distillation of the extract in an edible oil or fat to obtain a bland natural antioxidant. Fractionation and characterization of the active antioxidant ingredient in the extract of Rosemary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
146
2
11

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(163 citation statements)
references
References 3 publications
4
146
2
11
Order By: Relevance
“…The antioxidant activity displayed by spices or other antioxidants depends on several factors such as the concentration, the temperature, the hydrophobic, hydrophylic or amphiphatic character, the presence of synergists and the chemical nature of the food or medium to which they are added (Logouri and Boskou, 1995). Chang et al (1977) obtained similar results while investigating the antioxidative effect of rosemary and sage due to the peroxide value. Essential oils such as rosemary and sage oils lack any antioxidant activity although the herbs are known antioxidants and find many applications in food preparations (Chipault et a!., 1952;Chipault et a!., 1956;Bishou eta!., 1977;Hermann eta!., 1981;Barbut efa/., 1985;Pizzocaro eta!., 1985;Inatani et al, 1984;Houlihan et al, 1984;Ózcan and Akgül, 1995).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The antioxidant activity displayed by spices or other antioxidants depends on several factors such as the concentration, the temperature, the hydrophobic, hydrophylic or amphiphatic character, the presence of synergists and the chemical nature of the food or medium to which they are added (Logouri and Boskou, 1995). Chang et al (1977) obtained similar results while investigating the antioxidative effect of rosemary and sage due to the peroxide value. Essential oils such as rosemary and sage oils lack any antioxidant activity although the herbs are known antioxidants and find many applications in food preparations (Chipault et a!., 1952;Chipault et a!., 1956;Bishou eta!., 1977;Hermann eta!., 1981;Barbut efa/., 1985;Pizzocaro eta!., 1985;Inatani et al, 1984;Houlihan et al, 1984;Ózcan and Akgül, 1995).…”
Section: Introductionsupporting
confidence: 65%
“…Essential oils such as rosemary and sage oils lack any antioxidant activity although the herbs are known antioxidants and find many applications in food preparations (Chipault et a!., 1952;Chipault et a!., 1956;Bishou eta!., 1977;Hermann eta!., 1981;Barbut efa/., 1985;Pizzocaro eta!., 1985;Inatani et al, 1984;Houlihan et al, 1984;Ózcan and Akgül, 1995). Naturally occurring compounds in rosemary extracts (Wu etal., 1982;Ho etal., 1983) have been reported to exhibit antioxidant properties greater than BHA and equal BHT The extracts rosemary (Chang et al, 1977;Economou et al, 1991;Banlas et al, 1992), were examined in order to determine their antioxidative activity against autoxidation in different substrates, mostly in lard. Their antioxidative activity depends on the solvent used, but the structure activity relationship of them have not been completely investigated (Chang et al, 1977;Economou et al, 1991;Banlas eí a/., 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of these studies indicated clearly that the majority of the spices tested possessed some antioxidant activity, with rosemary (Rosmarinus officinalis L.) and sage (Salvia officinalis L.) being the most potent. Rosemary and sage are two plant sources of antioxidants that have been studied intensively and proven effective for stabilizing frying oils (11). Both antioxidants sources have very good thermal resistance and strong antioxidant characteristics (12,13).…”
Section: Jaswir Dd Kitts Yb Che Man Et Almentioning
confidence: 99%
“…[1,2,7,8,22,23,25,29,31,32]. A atividade antioxidante das especiarias e de seus extratos é atribuída aos compostos fenólicos [5,6] que também podem atuar como seqüestrantes de radicais livres no organismo reduzindo os riscos de doenças crônicas, [17].…”
Section: -Introduçãounclassified